ANALISIS KOROSI PIPA PENDINGIN SEKUNDER RSG-GAS DENGAN TEKNIK ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY (EIS) - Ajiriyanto, Maman Kartaman; Kriswarini, Rosika; Yanlinastuti, Yanlinastuti; Lestari, Diyah Erlina (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Multi-purpose reactor G.A. Siwabessy has a secondary cooling system facility to extract heat generated from uranium fission reactions in the reactor. The cooling pipe material is a type of carbon steel. Secondary cooling media is water supplied from Puspiptek. To extend the lifetime of the pipe, chemical compound ZnPO4 was put on the water-cooling media as a corrosion inhibitor. The corrosion analysis of secondary pipe was performed by corrosion testing using EIS and tafel method. The electrochemically corrosion test was performed with three electrode cells in water media, 0.05 M HCl solution and 3% NaCl solution. The aim is to obtain the optimum inhibitor concentration added in the secondary coolant and to determine the inhibition mechanical as well as the inhibitor efficiency. EIS testing was performed in the frequency range 100 kHz to 0.02 Hz in HCl 0,05M. Test results show changes in electrical parameters such as Rct, Cdl and Rs. The inhibitor concentration increases then Rct value increase. At inhibitor concentration of 90 ppm obtained the highest Rct value is 81,29 ohm. Efficiency of the inhibitor addition produces maximum value is 66,75% at concentration of 90 ppm. The corrosion rate in samples on medium of 3% NaCl without inhibitor, moss inhibitor and corrosion inhibitor were 3.975, 3.576 and 3.215 mpy respectively. The addition of a mixture of corrosion inhibitors and moss inhibitors can decrease the corrosion rate up to 1.586 mpy quantitatively. The addition of inhibitors using ordinary water may inhibit interface reactions on the surface of the sample as indicated by the higher the inhibitor concentration the higher the Rct value. In NaCl 3% medium also shows the same phenomenon relatively that the corrosion mechanism can be inhibited by increasing of Rct value as well as in this condition, Rs value is constant relatively. The dominant fact that the addition of a corrosion inhibitor could decrease the corrosion rate. The moss inhibitors have a primary function not to decrease the corrosion rate.